The factorization method for inverse scattering by a penetrable anisotropic obstacle with conductive boundary condition. (6th September 2016) - Bondarenko, Oleksandr; Kirsch, Andreas
Abstract: In this paper we consider a problem of scattering by a coated anisotropic dielectric. Our main focus is to show that the factorization method can be applied for reconstruction of the scattering object from the far field data. At the end we present some numerical results to demonstrate the feasibility of the method.